ANALISIS VARIASI TRANSMISI GEAR TERHADAP OUTPUT DAYA LISTRIK PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA PIKOHIDRO MENGGUNAKAN TURBIN TURGO - Hary Putra Darma, I Nyoman; Budiastra, I Nyoman; Arta Wijaya, I Wayan (Program Studi Teknik Elektro UNUD, 2023)
The design of the Picohydro Power Plant at the Kanto Lampo Waterfall tour was carried out to meet the electricity demand in the form of lighting in the area. Based on a survey that has been conducted, the access road from the parking lot to the waterfall is about 150 meters away and does not yet have adequate lighting. The waterfall has a height of 15 meters, so the design of the PLTPH prototype will use a turgo turbine to maximize the power output of the generator which is distributed to the lighting. This research was conducted to determine the effect of gear variations on rotational speed, torque, voltage, current and power produced by the PLTPH prototype. The test method used is direct testing on the prototype. The data obtained, then graphed the influence of gear variations with the parameters tested. All parameters tested get the highest rotation results by using 2 nozzles of 752.2 rpm. In the gear transmission test the highest output results were obtained at a ratio of 4:1 and the power generated was 48.70 watts.